'Two‐step' head‐to‐body delivery activates foetal gluconeogenesis. (3rd May 2013) - Zanardo, Vincenzo; de Luca, Federico; Trevisanuto, Daniele; Simbi, Alphonse; Scambia, Giovanni; Straface, Gianluca
Abstract: Aim: The 'two‐step' head‐to‐body delivery method, which involves waiting for the next contraction to deliver the shoulders, causes a decrease in umbilical artery pH. The aim of this study was to assess whether foetal acidemia activates gluconeogenesis. Methods: We tested umbilical artery cord blood glucose concentration and pH after 341 spontaneous and 25 vacuum extractor 'two‐step' vaginal deliveries (VD) and after 85 elective and 49 emergency caesarean sections (CS). Results: Cord blood glucose concentration was significantly higher (95.5 ± 21.4  mg/dL vs 75.6 ± 16.4, p < 0.001), and pH values significantly lower (7.31 ± 0.09 vs 7.33 ± 0.06, p = 0.003) in 'two‐step' VD neonates than in CS delivered neonates. In addition, cord blood glucose concentration was significantly higher (101.4 ± 30.6 mg/dL, p = 0.004), and pH values were significantly lower (7.26 ± 0.10, p < 0.001) in VD by vacuum extractor than in all other groups. The cord blood glucose concentration is significantly and negatively correlated with pH in the study population (r = −0.094, p = 0.036) and strongly significantly and negatively correlated in VD by vacuum extractor (r = −0.594, p = 0.007). Conclusion: Cord blood glucose concentrations are significantly higher and pH values significantly lower in 'two‐step' VD neonates, indicating activated foetal gluconeogenesis.